Algorithms and Architectures for Parallel Processing 8th International Conference, ICA3PP 2008, Cyprus, June 9-11, 2008 Proceedings - Bourgeois, Anu G.; Zheng, S. Q.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book constitutes the refereed proceedings of the 8th International Conference on Algorithms and Architectures for Parallel Processing, ICA3PP 2008, held in Agia Napa, Cyprus, in June 2008. The 31 revised full papers presented together with 1 keynote talk and 1 tutorial were carefully reviewed and selected from 88 submissions. The papers are organized in topical sections on scheduling and load balancing, interconnection networks, parallel algorithms, distributed systems, parallelization tools, grid computing, and software systems.
Smart Content Delivery on the Internet -- Parallel Query Processing in Databases on Multicore Architectures -- Evaluation of a Novel Load-Balancing Algorithm with Variable Granularity -- A Static Multiprocessor Scheduling Algorithm for Arbitrary Directed Task Graphs in Uncertain Environments -- An ACO Inspired Strategy to Improve Jobs Scheduling in a Grid Environment -- Architecture Aware Partitioning Algorithms -- A Simple and Efficient Fault-Tolerant Adaptive Routing Algorithm for Meshes -- Deadlock-Free Adaptive Routing in 2D Tori with a New Turn Model -- Neighbourhood Broadcasting and Broadcasting on the (n, k)-Star Graph -- Fault Tolerance in the Biswapped Network -- 3D Block-Based Medial Axis Transform and Chessboard Distance Transform on the CREW PRAM -- A General Approach to Predict the Performance Order of TSP Family Problems -- Examining the Feasibility of Reconfigurable Models for Molecular Dynamics Simulation -- Parallel Simulated Annealing for Materialized View Selection in Data Warehousing Environments -- An Operational Approach to Validate the Path of BGP -- 1-Persistent Collision-Free CSMA Protocols for Opportunistic Optical Hyperchannels -- An Optimization of Context Sharing for Self-adaptive Mobile Applications -- A Network Service for DSP Multicomputers -- A Non-blocking Multithreaded Architecture with Support for Speculative Threads -- Finding Synchronization-Free Parallelism Represented with Trees of Dependent Operations -- Lee-TM: A Non-trivial Benchmark Suite for Transactional Memory -- Performance of OpenMP Benchmarks on Multicore Processors -- Adaptive Loop Tiling for a Multi-cluster CMP -- Quasi-opportunistic Supercomputing in Grid Environments -- Explicit Control of Service Execution to Support QoS-Based Grid Scheduling -- Parallelization and Distribution Strategies of Large Bioinformatics Requests over the Grid -- Designing an Architecture for Distributed Shared Data on the Grid -- Grinda: A Tuple Space Service for the Globus Toolkit -- SuMo: A Framework for Prototyping Distributed and Mobile Software -- A Debugger for Parallel Haskell Dialects -- Introducing Aspects to the Implementation of a Java Fork/Join Framework -- Analyzing Software Component Graphs of Grid Middleware: Hint to Performance Improvement -- Using Multi-core to Support Security-Related Applications -- Symbolic Analysis for Increased Program Execution Performance.
Keywords: Computer science; Computer organization; Software engineering; Computer programming; Computers; Algorithms; Computer engineering; Computer Science; Software Engineering/Programming and Operating Systems; Computer Engineering; Programming Techniques; Computer Systems Organization and Communication Networks; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Electronic books